2016
DOI: 10.3389/fmicb.2016.01644
|View full text |Cite
|
Sign up to set email alerts
|

FlhF Is Required for Swarming Motility and Full Pathogenicity of Bacillus cereus

Abstract: Besides sporulation, Bacillus cereus can undergo a differentiation process in which short swimmer cells become elongated and hyperflagellated swarmer cells that favor migration of the bacterial community on a surface. The functionally enigmatic flagellar protein FlhF, which is the third paralog of the signal recognition particle (SRP) GTPases Ffh and FtsY, is required for swarming in many bacteria. Previous data showed that FlhF is involved in the control of the number and positioning of flagella in B. cereus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…So far, all B. thuringiensis isolates in this study showed the genetic premises (presence of enterotoxin genes) to provoke the diarrhoeal type of food poisoning. Nevertheless, prerequisites for B. cereus enterotoxin production and cytotoxicity are also spore germination [ 14 , 40 , 41 , 42 , 43 ] and motility [ 14 , 44 , 45 , 46 ] in the host’s intestine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, all B. thuringiensis isolates in this study showed the genetic premises (presence of enterotoxin genes) to provoke the diarrhoeal type of food poisoning. Nevertheless, prerequisites for B. cereus enterotoxin production and cytotoxicity are also spore germination [ 14 , 40 , 41 , 42 , 43 ] and motility [ 14 , 44 , 45 , 46 ] in the host’s intestine.…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the potential health risk originating from (biopesticidal) B. thuringiensis isolates in more detail, we additionally investigated germination and motility behaviour of the strain set, which are further crucial prerequisites for the onset of the diarrhoeal disease [ 14 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Although different germination patterns emerged, spores of most isolates were able to germinate, even in cRPMI medium with preceding heat treatment mimicking re-heating of stored foods and subsequent consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In routine diagnostics, the enteropathogenic potential of a new isolate is so far determined via its ability to produce enterotoxins after growth under standard laboratory conditions ( Jessberger et al, 2015 ). However, in the meantime B. cereus food infections are rather understood as multifactorial processes including various steps such as (i) the survival of spores during stomach passage ( Clavel et al, 2004 ; Wijnands et al, 2009 ; Ceuppens et al, 2012a ; Berthold-Pluta et al, 2015 ), (ii) germination of spores in the small intestine ( Clavel et al, 2004 ; Wijnands et al, 2006 , 2007 ),(iii) motility ( Ghelardi et al, 2007 ; Salvetti et al, 2007 ; Mazzantini et al, 2016 ), (iv) adhesion of spores and vegetative cells to the intestinal epithelium ( Minnaard et al, 2004 ; Ramarao and Lereclus, 2006 ), and afterward (v) the production of enterotoxins under intestinal conditions ( Jessberger et al, 2017 ). Furthermore, the impact of complex foodstuffs has also been tested, mainly focusing on bacterial survival.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria employ many appendages for movement and dispersal in their ecological niches 9 . Flagella-enabled swarming offers bacteria a competitive advantage in both ecological and clinical settings 10,11 . An unexpected and clinically relevant property of swarms is their SR at conditions lethal to free-swimming planktonic cells of the same species 2-5,12 .…”
Section: Mainmentioning
confidence: 99%
“…S1a, b). At low concentrations (e.g, Kan 2.5 ; 2.5μg/ml), and during the early phase of growth (0.5 h), swarm cells were surprisingly more susceptible to killing than planktonic cells, a trend maintained for up to Kan 10 (Fig. S1a).…”
Section: Death Of a Sub-population May Be Linked To Strivementioning
confidence: 99%